2017
DOI: 10.1210/jc.2017-00308
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Anti-Müllerian Hormone System by Steroids in Women With Polycystic Ovary Syndrome

Abstract: In GCs from women with PCOS, the regulation of AMH and AMHR2 expression is altered in a way that promotes the overexpression of the AMH/AMHR2 system, and could contribute to the follicular arrest observed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…We also noticed that in the highest AMH quartile, E 2 levels correlated with AMH only in the PCOS group. In nonpregnant women with PCOS, E 2 has been reported to correlate with AMH both negatively (37) and positively (38), but in most studies no correlation has been detected (24,32,39). Previously an in vitro study demonstrated a lack of E 2 -mediated AMH down-regulation in granulosa cells from women with PCOS (40).…”
Section: Discussionmentioning
confidence: 98%
“…We also noticed that in the highest AMH quartile, E 2 levels correlated with AMH only in the PCOS group. In nonpregnant women with PCOS, E 2 has been reported to correlate with AMH both negatively (37) and positively (38), but in most studies no correlation has been detected (24,32,39). Previously an in vitro study demonstrated a lack of E 2 -mediated AMH down-regulation in granulosa cells from women with PCOS (40).…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with 5-adihydrotestosterone yielded similar results [30]. Furthermore, although estrogens suppress AMH expression, mediated via estrogen receptor b, in normoovulatory women, this suppression was not observed in granulosa cells of anovulatory PCOS women [30,31]. Combined, these results suggest a failure in the downregulation of AMH expression in gonadotropindependent follicular stages in PCOS, which may contribute to a failure in follicular growth.…”
Section: Amh and Its Role In Ovarian Function In Pcosmentioning
confidence: 58%
“…Combined with the elevated LH levels in PCOS, this leads to hyperstimulation of the theca cells and premature luteinization of granulosa cells. Interestingly, LH stimulation increased AMH expression in granulosa cells of PCOS women but not in normoovulatory women [24,29,30]. Treatment with 5-adihydrotestosterone yielded similar results [30].…”
Section: Amh and Its Role In Ovarian Function In Pcosmentioning
confidence: 81%
See 1 more Smart Citation
“…A handful of hormones regulating AMHR2 expression have been identified so far, mostly from studies on ovarian tissues. FSH and estradiol were reported to downregulate Amhr2 transcripts in rat ovarian follicles [37], and an inhibitory effect of LH and estradiol on AMHR2 mRNA levels was reported in human luteinized granulosa cells [38, 39]. Contrasting with gonadotropins, bone morphogenetic protein 4 (BMP4) and BMP15 were recently demonstrated to upregulate AMHR2 mRNA levels in human granulosa cells through transcriptional activation of the AMHR2 promoter [40].…”
Section: Introductionmentioning
confidence: 99%